Discovery of compounds that reactivate p53 mutants in vitro and in vivo. Issue 9 (15th September 2022) - Durairaj, Geetha; Demir, Özlem; Lim, Bryant; Baronio, Roberta; Tifrea, Delia; Hall, Linda V.; DeForest, Jacob C.; Lauinger, Linda; Jebril Fallatah, Maryam M.; Yu, Clinton; Bae, Hosung; Lin, Da-Wei; et al.
Summary: The tumor suppressor p53 is the most frequently mutated protein in human cancer. The majority of these mutations are missense mutations in the DNA binding domain of p53. Restoring p53 tumor suppressor function could have a major impact on the therapy for a wide range of cancers. Here we report a virtual screening approach that identified several small molecules with p53 reactivation activities. The UCI-LC0023 compound series was studied in detail and was shown to bind p53, induce a conformational change in mutant p53, restore the ability of p53 hotspot mutants to associate with chromatin, reestablish sequence-specific DNA binding of a p53 mutant in a reconstituted in vitro system, induce p53-dependent transcription programs, and prevent progression of tumors carrying mutant p53, but not p53 null or p53 WT alleles. Our study demonstrates feasibility of a computation-guided approach to identify small molecule corrector drugs for p53 hotspot mutations. Graphical abstract: Highlights: Small molecules targeting a cryptic L1/S3 pocket of p53 are identified Experimental validation led to the identification of mutant p53 reactivators Compounds restore DNA binding of p53 MUT in vitro and in vivo Compounds directly bind to p53 MUT and exert anti-tumor effect in tumor models Abstract : A large fraction of human tumors inactivate the major tumor suppressor p53 by mutations. Corrector drugs reactivating mutant p53 are of high clinical value for cancer therapy. Durairaj et al. identify small drug-like compounds that restore wild-type activity to mutant forms of p53 and exhibit anti-tumor effects.